IDENTIFIKASI FAKTOR PENYEBAB KESULITAN MENCATAT TRANSAKSI KE JURNAL UMUM PERUSAHAAN JASA SMA WISUDA PONTIANAK - Yunani, Lisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aims to know cause factor difficult of students study in noting transaction to common journal of company service class XI social of senior high school Wisuda Pontianak. In this research the method used is approach of qualitative which form descriptive. Data selection technic used is direct observation, direct communication and documentary study technic, while, the instrument for data collection are observation, interview, and documentation. analysis in this research is given as descriptive qualitative using seven students informant who have difficulties in studying of common journal. Research result?s got that preparation factor in studying, want study, learning motivation, studying habitual, teacher of subject lesson (way of teacher teaching) and study resource (lesson books) cause student gets difficult of studying in noting transaction to common journal of service company class XI social of senior high school Wisuda Pontianak, and the most dominant foctor is willing study and studying motivation. Keywords: cause, difficult of study, common journal